SENTINEL1: Two-Season Study of Respiratory Syncytial Virus Hospitalizations among U.S. Infants Born at 29 to 35 Weeks' Gestational Age Not Receiving Immunoprophylaxis - Anderson, Evan J.; DeVincenzo, John P.; Simões, Eric A. F.; Krilov, Leonard R.; Forbes, Michael L.; Pannaraj, Pia S.; Espinosa, Claudia M.; Welliver, Robert C.; Wolkoff, Leslie I.; Yogev, Ram; Checchia, Paul A.; Domachowske, Joseph B.; Halasa, Natasha; McBride, Scott J.; Kumar, Veena R.; McLaurin, Kimmie K.; Rizzo, Christopher P.; Ambrose, Christopher S. (American Journal of Perinatology, 2020)
Objective The SENTINEL1 observational study characterized confirmed respiratory syncytial virus hospitalizations (RSVH) among U.S. preterm infants born at 29 to 35 weeks' gestational age (wGA) not receiving respiratory syncytial virus (RSV) immunoprophylaxis (IP) during the 2014 to 2015 and 2015 to 2016 RSV seasons.Study Design All laboratory-confirmed RSVH at participating sites during the 2014 to 2015 and 2015 to 2016 RSV seasons (October 1–April 30) lasting ≥24 hours among preterm infants 29 to 35 wGA and aged <12 months who did not receive RSV IP within 35 days before onset of symptoms were identified and characterized.Results Results were similar across the two seasons. Among infants with community-acquired RSVH (N = 1,378), 45% were admitted to the intensive care unit (ICU) and 19% required invasive mechanical ventilation (IMV). There were two deaths. Infants aged <6 months accounted for 78% of RSVH observed, 84% of ICU admissions, and 91% requiring IMV. Among infants who were discharged from their birth hospitalization during the RSV season, 82% of RSVH occurred within 60 days of birth hospitalization discharge.Conclusion Among U.S. preterm infants 29 to 35 wGA not receiving RSV IP, RSVH are often severe with almost one-half requiring ICU admission and about one in five needing IMV.
Keywords: respiratory syncytial virus; infants; palivizumab; immunoprophylaxis; hospitalizations